The Effect Of Company Size, Liquidity, And Profitability On Company Value (Empirical Studies On Food And Beverage Subsector Companies Listed On The Indonesia Stock Exchange In 2016-2020) - Kevin Kevin; Sabam Simbolon (Primanomics : Jurnal Ekonomi & Bisnis, 2022)
This study aims to obtain empirical evidence regarding the effect of company size, liquidity, and profitability on company value. The population in this study is the financial statements of food and beverage subsector companies listed on the IDX 2016-2019.The samples were determined using purposive sampling with a total sample size of 10 companies during a period of 5 years of observation so that the total sample was 50. The research data were analyzed using multiple linear regression analysis method to determine the research method with SPSS application version 25.The result of this study indicate that the company size variable has a negative and insignificant effect on company value, liquidity has a positive and significant effect on company value, profitability has a positive and significant effect on company value on food and beverage subsector companies listed on the Indonesia Stock Exchange in 2016-2020.The results show that company size, liquidity, and profitability have an effect on company value.